Tridax coronopifolia var. alboradiata (Asteraceae) essential oil: chemical characterization and repellent potential against Sitophilus zeamais (Coleoptera: Curculionidae) - Gómez-Sosa, Lilibeth; Pérez-Pacheco, Rafael; Zárate-Nicolás, Baldomero Hortencio; Ortiz-Hernández, Yolanda Donají; Vásquez-López, Alfonso; Aquino-Bolaños, Teodulfo; Quiroz-González, Beatriz; Martinez-Tomas, Sabino H.; Arroyo-Balán, Fabián; Fonseca-Muñoz, Alicia; Granados-Echegoyen, Carlos (Frontiers in Agronomy, 2025)
Currently, on a global level, there are major difficulties in pest control during the storage of grains and cereals. The most widely used method is the use of synthetic insecticides, a practice that pollutes the environment and causes health problems for consumers. As a result of this problem, this study evaluated the repellent effect of essential oil from Tridax coronopifolia var. alboradiata against Sitophilus zeamais. The oil was extracted via microwave-assisted hydrodistillation and characterized using gas chromatography. Repellency bioassays were conducted at concentrations of 50, 100, 200, 400, 600, and 800 ppm, with both positive and negative controls. The essential oil exhibited significant repellent activity against S. zeamais. At 800 ppm, the selection index was 0.27, indicating high repellency and a clear preference of insects for untreated maize grains. Chemical analysis revealed sixteen terpenes, accounting for 98.43% of the total volatile content. The predominant compounds were 2-carene (24.1%), camphene (12.6%), α-pinene (10.23%), and hexadecanal (9.11%). These results confirm the efficacy of T. coronopifolia var. alboradiata essential oil as a repellent against S. zeamais and underscore its potential as a botanical insecticide. The chemical profile provides valuable information to support its development as a sustainable alternative for managing stored grain pests.